2010
DOI: 10.2981/08-051
|View full text |Cite
|
Sign up to set email alerts
|

Investigating population dynamics in ungulates: Do hunting statistics make up a good index of population abundance?

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 23 publications
1
63
0
1
Order By: Relevance
“…Population density estimates are obtained from the data base of bag records described by Imperio et al (2010). Data are available for the period 1878 to 1986 (records are missing in nine out of 109 years, mostly during the two World Wars, thereafter WWI and WWII) and are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Population density estimates are obtained from the data base of bag records described by Imperio et al (2010). Data are available for the period 1878 to 1986 (records are missing in nine out of 109 years, mostly during the two World Wars, thereafter WWI and WWII) and are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Density estimates ( N t ) were computed as the number of specimens killed during hunting drives, per km 2 of driven area. The quality of collected data and their validity for the assessment of population density are discussed by Imperio et al (2010), which showed no relevant bias due to hunting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Italy, hunting statistics were widely explored by Boitani et al (1995), and subsequently, they were used to investigate long time-trend series of wild boar (Imperio et al 2010). weather, food availability and population density), and (4) variability due to non-hunted populations in urban and protected areas.…”
Section: Hunting Bag Statisticsmentioning
confidence: 99%